Effects of dietary inclusion of ginger (Zingiber officinale) and garlic (Allium sativum) oil (GGO) mixtures on carcass characteristics and sensory evalaution of broiler chickens - Oluwafemi, R.A; Lawal, Aisha Omolade; Adelowo, Samad Adetope; Alagbe, J.O (Zien Journals, 2021)
An experiment was carried out to examine the effect of dietary inclusion of ginger (Zingiber officinale) and garlic (Allium sativum) oil (GGO) mixtures on the carcass characteristics and sensory evaluation of broiler chickens. A total of 120 one-day-old (Arbo acre) were divided into five treatments with three replicates per treatment consisting of 8 birds each in a completely randomized design. Clean feed and water were provided ad libitum throughout the experiment which lasted for 8 weeks. Basal diet was formulated to meet the nutritional requirement of birds according to NRC (1994). Birds in treatment 1 (T1) were fed diet supplemented with 0 % GGO while T2, T3, T4 and T5 were fed GGO at 0.1 %, 0.2 %, 0.3 % and 0.4 % respectively. Results obtained were used to examine the phytochemical composition of (Zingiber officinale) and garlic (Allium sativum) oil as well as carcass and organ characteristics of birds. Phytochemical composition of Zingiber officinale revealed the presence of phenols (8.21 %), alkaloids (5.12 %), flavonoids (7.49 %), tannins (6.52 %), saponins (3.18 %), streiods (2.38 %), glycosides (0.18 %), oxalates (0.07 %) and phytate (0.02 %). Allium sativum contains flavonoids (10.67 %), phenols (9.19 %), alkaloids (7.02 %), tannins (4.72 %), steroids (3.65 %), saponins (2.40 %), glycosides (0.33 %), oxalates (0.26 %), phytate (0.05 %). Dressing percentage, carcass and relative organ weights were significantly (P <0.05) among the treatments. There was no noticeable inflammation observed in the liver, kidney, spleen, liver and other internal organs. Sensory evaluation of the meat (tenderness, juiciness, flavor and aroma) were significantly (P><0.05) influenced by GGO except the meat colour which was not significantly (P˃0.05) different among the treatments. It was concluded that GGO can be included up to 0.4 % in the diet of broilers without causing any deleterious effect on the health and performance of birds.
Keywords: Broilers; Ginger; Garlic; Phytochemicals